Influence of underlying local organisations in typical nematic phase of 6CHBT and induced nematic phase of bicomponent liquid crystalline systems 4DBT–12CB – a Fast Field Cycling NMR investigation. Issue 10 (9th August 2017) - Phani Kumar, B. V. N.; Mattea, C.; Stapf, S.; Dabrowski, R.
ABSTRACT: Variable-temperature proton magnetic relaxation dispersion (PMRD) profiles are collected in the induced nematic phases of the binary liquid crystalline mixtures composed of smectic mesogens: 5-butyl-2-(4-isothiocyanatophenyl)-1, 3-dioxane (4DBT) and 4′-dodecyl-4-cyanobiphenyl (12CB) and the low viscous nematogen 4-(trans-4′-n-hexylcyclohexyl)-isothiocyanatobenzene (6CHBT), with a view to assess the influence of local organisations on the power spectrum of director fluctuation modes. Two distinct compositions of the binary mixture i.e. 50 mol% of 12CB (without a smectic phase) and 70 mol% of 12CB (with a smectic phase) are used. Fast Field Cycling nuclear magnetic resonance relaxometry is employed to measure proton spin-lattice relaxation rates ( R1 ) as a function of Larmor frequency (10 kHz–30 MHz). PMRD data analysis with the choice of a suitable model indicated nematic clusters of moderate size ( 200 Å) found in the broad nematic region of 50 mol% 12CB, whose size is almost invariant with temperature. On the other hand, cybotactic clusters, i.e. local smectic organisations of relatively larger size ( 2000–3000 Å), are observed near the nematic–smectic transition (T > TAN ) of 70 mol% 12CB. Interestingly, the shape geometry of such local organisations accessed from PMRD analysis is weakly anisotropic near TAN, while being isotropic near TNI for 70 mol% 12CB. GRAPHICAL ABSTRACT: